Coinfection Between Amoebic Liver Abscess Caused By Entamobea histolytica And Hepatitis A in AL-Najaf Governorate - Mohammed, Eman Hamza; Shnain Al-Abbas, Wijdan Dhaidan; Sarhan, Nadia Habeeb (Medical Science Journal for Advance Research, 2024)
Background: It was the goal of the current research study to determine the link between hepatitis a virus infection and amoebic liver abscess, as well as to determine the effects of hepatitis a viruses and amoebic liver abscess on the serum levels of biochemical markers such as IL-2, IL-8, and IL-10 (ALP, ALT, AST and TSB) From February 2021 to January 2022, the current study was conducted. Patients from Al Furat General Hospital in AL-Najaf Province, Al Sader General Hospital, AL-Zahra maternity and pediatrics, and AL-Hakeem Hospital have been referred to this laboratory for testing. Hepatitis A infection and amoebic liver abscess coinfection were both more common in men than in women, according to the findings of the current study. Hepatitis A was found to be most prevalent in males between the ages of 8 and 17 and females between the ages of 18 and 27 in the current investigation. Results from the current study show that interleukin 2 concentrations rose in coinfections between amoebic liver abscess and Hepatitis A at a rate of (13.572-8341.2) compared to Hepatitis A (11.113-873.4) and Amoebic liver abscess (8.789-473.2). However, interleukin 8 concentrations rose to the highest level in Amoebic liver abscess (12.32-555.43) compared to Hepatitis A (5.765-64.5). (35-322.8), Coinfection between amoebic liver abscess and Hepatitis A was shown to have the highest level of ALT (9.19-812.2) compared to Hepatitis A (23.8-102.6) and Amoebic liver abscess (32.12-50.1) ,(0.12-3.32).